Desain Ikon untuk Tunanetra pada Kemasan Bahan Pokok Makanan - Sucipto, Fentisari Desti; Yuda, Rino; Sastrawijaya, Reza (Universitas Bumigora, 2022)
The development of times and technology requires each individual to be able to do their activities more easily, practically and quickly. This phenomenon does not only affect people with normal physical condition, but it also affects people with disability. Therefore, there are many designs focusing on and orientating towards solution to facilitate people with disability do their daily activities, especially when they are in in public facilities. One of the most frequently visited public facilities is shopping center (traditional market, mini market and supermarket). The researcher found that people with disability, especially those with visual impairment find difficulties to do shopping independently. Based on this problem, the researcher offers solution by designing icons for product sold in the market and the focus was on the staple food products consumed every day. This was qualitative research with design thinking method. The results showed that icon design on staple food packages can help people with visual impairment to identify staple food products.